(391) Lectures of Methods of Optimization. محاضرات في طرق الأمثلية - Saaty, T. L. (معهد التخطيط القومى, 2024)
the following set lectures follow the material which appeared in my books "Mathematical Methods of operations research" and Nonlinear Mathematics" Optimization, maximization, minimization and minimax of game theory, is a basic subject in mathematics which has come to play significant role in modern technology.